Technological anthropocentrism in accounting for Industry 5.0 - Muravskyi, Volodymyr; Pytel, Sviatoslav; Bashutskyy, Roman (Herald of Economics, 2025)
Introduction. The emergence of the Fifth Industrial Revolution emphasizes technological anthropocentrism as a concept for managing enterprises based on accounting information and leveraging advanced computer-communication technologies. Industry 5.0 focuses particularly on the critical role of modern computer-communication technologies in realizing anthropocentric priorities within the societal framework, particularly in the financial and economic activities of enterprises.The purpose of the article is to position the anthropocentric concept of enterprise management based on accounting information as an informational component of Industry 5.0, utilizing state-of-the-art computer-communication technologies.Methods. The study of accounting transformation prospects in the context of Industry 5.0 employed general scientific empirical, logical, and historical methods of cognition. The research is based on general methods of analyzing economic processes, facts, and phenomena from the perspectives of accounting and computer technologies.Results. It is substantiated that technological anthropocentrism is becoming a key concept in enterprise management, grounded in the implementation of opportunism, behaviorism, agency theory, and institutionalism. The main directions for implementing anthropocentrism in Industry 5.0 accounting include adherence to robotics laws, optimization of working time, stimulation of creativity, professional development, and meeting stakeholders’ informational needs. It is noted that technological anthropocentrism contributes to mitigating informational, reputational, and socio-economic risks while supporting the socio-economic interests of society, professionals, and state institutions.Prospects. The process of establishing technological anthropocentrism is ongoing and multifaceted, highlighting new aspects of accounting transformation in the context of the development of innovative computer-communication technologies. This necessitates further research in the realm of Industry 5.0.